Pachner Move 3 → 3 and Affine Volume-Preserving Geometry in R³ - Korepanov, I.G. (Symmetry, Integrability and Geometry: Methods and Applications, 2005)
Pachner move 3 → 3 deals with triangulations of four-dimensional manifolds. We present an algebraic relation corresponding in a natural way to this move and based, a bit paradoxically, on three-dimensional geometry.